Two-way shape memory effect and thermal cycling stability in Co35Ni35Al30 single crystals by low-temperature martensite ageing. (June 2018) - Panchenko, E.; Eftifeeva, A.; Chumlyakov, Y.; Gerstein, G.; Maier, H.J.
Abstract: Low-temperature stress-induced martensite ageing at 400 K under a compressive stress of −500 MPa was applied along the [110]B2 ||[100]L10 -direction for improving the functional properties of ferromagnetic Co35 Ni35 Al30 single crystals, which feature a B2-L10 martensitic transformation. Along the [001]B2 -direction the stress-induced martensite aged crystals demonstrated a two-way shape memory effect with a giant reversible tensile strain of up to +7.3 (±0.3) % and a high functional stability during stress-free cooling/heating cycles. In addition, a rubber-like behavior with a reversible compressive strain of up to −4.4 (±0.3) % in loading/unloading cycles in the L10 -martensite was observed. Graphical abstract: Unlabelled Image